Analysis of the novel cross vane expander-compressor : mathematical modelling and experimental study - Yap, Ken Shaun (2020)
One of the challenges in cooling science today is the development of vapour compression system that is compact, scalable and highly energy-efficient. In order to achieve this goal, the novel cross vane expander-compressor (CVEC) has been introduced. This device amalgamates the working principle of the compressor and expander into a single unit, permitting fluid compression and expansion energy recovery to be accomplished simultaneously. In this paper, we describe theoretically the frictional losses of the CVEC and predict its net power input per cycle. CO2 is used as the working fluid for simulation purposes. The mechanical efficiency of CVEC is found to be 95.9% where the largest loss is caused by end-face friction which accounts for 81.2% of the total losses. The proposed CVEC system improves the overall coefficient of performance (COP) by 36.6% as compared to that of the basic vapour compression system. An experimental investigation is conducted for the measurement of torque and speed of a CVEC prototype to verify its operational characteristics. For initial testing purposes, air is used as the working fluid in an open circuit. The average discrepancy between the predicted and measured net power input was found to be 10.5%.